Response of ultra-high strength quenched and tempered steel plates to heat - Azfar Sa'ad (2014)
Grade S690 has a much higher tensile strength than the common grades that is used in the industry. Due to this high strength, using S690 will promote the design of leaner structures with increased energy efficiency and easier transportation of the materials. However, the strength of the steel greatly decreases after being exposed to high temperatures. Therefore welding will also reduce the joints strength compared to the base metal. Furthermore, welding will cause the metal to be brittle and gain a lot of residual stress.